2015
DOI: 10.1108/jfep-03-2015-0018
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory capital and its effect on credit growth, non-performing loans and bank efficiency

Abstract: Emerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series volumes, as well as providing an extensive range of online products and additional customer resources and services. Emerald is both COUNTER 4 and TRANSFER compliant. The organization is a partner of the Committee on Publication Ethics (COPE) and also works with Portico and the LOCKSS initiative for digital archive preservation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 30 publications
9
16
0
Order By: Relevance
“…It could be concluded that the variable return on assets has a significant effect on stock returns. This finding supported the results of researches conducted by Rottke and Gentgen (2008), Boudriga et al (2009), Laryea et al (2016), and Assibey and Asenso (2015).…”
Section: Effect Of Non-performing Loan On Stock Returnsupporting
confidence: 91%
“…It could be concluded that the variable return on assets has a significant effect on stock returns. This finding supported the results of researches conducted by Rottke and Gentgen (2008), Boudriga et al (2009), Laryea et al (2016), and Assibey and Asenso (2015).…”
Section: Effect Of Non-performing Loan On Stock Returnsupporting
confidence: 91%
“…Therefore, we expected a positive relationship between BPR and NPL. This is also supported by an earlier study (Osei-Assibey & Asenso, 2015).…”
Section: Controlling For Macro-economic Variablessupporting
confidence: 90%
“…Therefore, a regulatory framework was devised by implementing minimum regulatory capital requirements in the shape of Basel Accords. Likewise, minimum capital requirements are extremely essential, whereas, overly stringent capital adequacy requirements can also hamper credit expansion (Osei-Assibey & Asenso, 2015). Karim et al (2014) conducted a study in 14 organizations of Islamic Conference (OIC) countries from the year 1999 to 2009 and found a positive relationship between capital adequacy requirements and loan growth in Islamic and conventional banks.…”
Section: Regulatory Capital and Credit Growthmentioning
confidence: 99%
“…It shows that the higher the capital owned by banks the higher lending given to the borrowers by banks. Banks with higher capital than the capital requirements by the government tend to give a higher lending as stated in [14] that found the same result of banking in Ghana and in line with [13] that there is relationship between capital and bank lending. The lacking of banks' capital will affect the lending decision of banks because it will cause the obstacle for the banks liquidity.…”
Section: Resultssupporting
confidence: 68%